The Influence of Service Quality and Price on Customer Loyalty through Customer Satisfaction as an Intervening Variable (Study at LBB SSL Sidoarjo) - Fadilah Lailatul Maghfiroh; Dwi Yuli Rakhmawati (STKIP Taman Siswa Bima, 2024)
This research was conducted to determine the effect of service quality and price on customer loyalty through customer satisfaction as an intervening variable at the Sang Siroju Lillah Sidoarjo Tutoring Institute. This research uses quantitative methods. The population in the research were students at the Sang Siroju Lillah Tutoring Institute at elementary, middle and high school levels. The number of samples used in this research was 114 students and used probability sampling which provides equal opportunities for all populations to be sampled. Data was analyzed using the SmartPLS method which went through three stages, namely internal model analysis, external model analysis, and hypothesis testing. Based on research, it shows: 1) service quality and price have a partial effect on customer loyalty, 2) service quality and price have a partial effect on customer satisfaction, 3) customer satisfaction has an effect on customer loyalty, 4) customer satisfaction does not affect customer loyalty so the relationship does not The direct relationship between service quality and customer loyalty through customer satisfaction cannot be verified, while price influences customer loyalty through customer satisfaction which can be verified.